Budidaya Tanaman Buah Jambu Demi Masyarakat yang Lebih Baik - Septanta, Rananda; Nurhasan, Yunus; Hidayat, Raden Ai Lutfi; Ramdhani, Chaeru Syahru (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Red guava leaves are a type of medicinal plant that has many health benefits, including treating diarrhea in young children, reducing bad cholesterol (LDL) levels, preventing cancer, healthy skin, treating hair loss, treating gum disease, and a natural cure for diabetes. . The purpose of this community service is to provide information on how to increase the potential of natural resources located in Pamulang, which is an area that has quite high potential in the guava plant business in general, but currently it has not been utilized optimally by the local community at this time. Most of the guava plants that are produced are immediately sold individually without knowing the harvest that is consumed. This is due to a lack of innovation from the local community. Therefore, guava cultivation is one way that can be done by harvesting quite small or large areas of land that can be put to good use, maintain nutritional value, and increase economic value. With this cultivation empowerment, it is hoped that it can help improve the economy of the Pamulang community and take advantage of the harvest of guava plants for social welfare which is more durable to give rise to various innovations in guava processing itself in a sustainable manner.